Coexistence of Negative Differential Resistance and Resistive Switching Memory at Room Temperature in TiOx Modulated by Moisture. (11th January 2018) - Zhou, Guangdong; Duan, Shukai; Li, Ping; Sun, Bai; Wu, Bo; Yao, Yanqing; Yang, Xiude; Han, Juanjuan; Wu, Jinggao; Wang, Gang; Liao, Liping; Lin, Cunyan; et al.
Abstract: Coexistence of negative differential resistance (NDR) and resistive switching (RS) memory is observed using a Ag|TiO x |F‐doped‐SnO2 memory cell at room temperature. Unlike other reports, the coexistence of NDR and RS strongly depends on the relative humidity levels at room temperature. The NDR disappears when the cells are placed in a dry air ambient (H2 O < 5 ppm) or in vacuum, but the coexistence emerges and gradually becomes obvious after the cells are exposed to ambient air with relative humidity of 35%, and then becomes dramatically enhanced as the relative humidity becomes higher. Due to the excellent stability and reversibility of the coexistence of NDR and RS, a multilevel RS memory is developed at room temperature. Hydroxide ion (OH − ) is induced by gas‐phase water‐molecule splitting on the surface and interface of the memory cell. The OH − interacts with oxygen vacancies and transports in the bulk of memory cell to facilitate the migration of Ag ions and oxygen vacancies along grain boundaries. These processes are responsible for the moisture‐modulated and room‐temperature coexistence. This work demonstrates moisture‐modulated coexistence of NDR and RS for the first time and gives an insight into the influence of water molecules on transition‐metal‐oxide‐based RS memory systems. Abstract : A moisture ‐dependent coexistence of negative differential resistance and resistive switching memory is realized using a Ag|TiO x |F‐doped‐SnO2 memory cell at room temperature. Water molecules interplay with oxygen vacancy to facilitate migration of Ag ions and oxygen vacancies along grain boundaries, which makes the moisture modulation of the coexistence behavior feasible.